Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1007/bf02427606
|View full text |Cite
|
Sign up to set email alerts
|

Long-term survival in a patient with supratentorial glioblastoma: clinical considerations

Abstract: Glioblastoma, a malignant tumor of neuroepithelial origin, is relatively uncommon in childhood, during which it accounts for 7%-9% of brain tumors. A few patients (about 3%) live more than 5 years. We report a 13-year-old girl who was admitted because one month earlier she had begun to present headache and diplopia. Brain computed tomography (CT) showed a right frontal tumor. At operation, complete excision of the visible tumor was performed. Histologic examination showed that the tumor was a glioblastoma mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
(28 reference statements)
1
5
0
Order By: Relevance
“…The majority of patients reported in case reports and case series that are thought to have been cured (from a clinical perspective) are in the younger age categories, which is consistent with the results of this study [3,4,5,6,30]. Vertosick and Selker [31] published a series of patients treated at their institution and suggested that cure may occur in GBM patients after 4 years of survival due to the low rates of recurrence (1 of 22 patients with GBM and high-grade gliomas).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The majority of patients reported in case reports and case series that are thought to have been cured (from a clinical perspective) are in the younger age categories, which is consistent with the results of this study [3,4,5,6,30]. Vertosick and Selker [31] published a series of patients treated at their institution and suggested that cure may occur in GBM patients after 4 years of survival due to the low rates of recurrence (1 of 22 patients with GBM and high-grade gliomas).…”
Section: Discussionsupporting
confidence: 81%
“…Studies are showing that only 2.2% of patients are estimated to survive 3 years or more after diagnosis of a GBM, a figure that is nevertheless set to increase in the near future due to recent therapeutic advances [1,2]. However, there are reports that some patients can live for more than 10 years after diagnosis and potentially achieve cure [3,4,5,6,7]. A common feature amongst those patients who live longer than 10 years is that they are typically younger than 40 years at the time of diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Genotyping was added to the new WHO classification of the central nervous system in 2016 (14), which makes accurate pathological grading as well as molecular and genotyping of glioma patients before surgery more urgent. In the treatment of glioma, conventional surgical excision plus radiotherapy can only prolong the average life span by 9–12 months (15) and does not effectively improve the prognosis of the patients. An important reason is the malignant biological behavior of gliomas, which includes the formation of neovascularization, malignant proliferation of cells, and invasive growth of the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…collective of patients is homogeneous with respect to localization (superficial cortical tumors) and age (no patients <20 years). This is an important point, since glioblastomas in childhood may show a more favourable clinical behaviour (22) and tumors from other sites such as deep-seated tumors may exhibit a different expression profile (23). Due to the standard postoperative treatment (local radiation with 60 Gy), even effects of different treatment modalities on survival time could be excluded.…”
Section: Discussionmentioning
confidence: 99%